Sistem Pemantauan Hasil Tampung Nira Kelapa Berbasis IoT (Internet of Things) - Daru Quthni Firdaus; Ali Rizal Chaidir; Wahyu Muldayani; Guido Dias Kalandro; Dodi Setiabudi (Politeknik Aceh, 2022)
An IoT-based monitoring system is a system that can monitor the situation by utilizing an internet connection. This system can be applied to simplify a production process, for example monitoring the results of the storage of coconut sap. Nira is a liquid from coconut flowers which has a sugar content ranging from 7.5 to 20%. The way to get sap is to climb a coconut tree and put the container on top, then wait for the container to fill up with sap. The monitoring process can be simplified by utilizing IoT technology. There is a sensor installed in the container, namely a water level float sensor which functions as a sensor to monitor the results of the storage of sap. The sensor provides information to the user via the eps8266 electronic board and LoRa module. Information can be read by users through the telegram application. The results of the test show that the water level float sensor can detect coconut sap that has filled the container. The use of the LoRa SX1278 module is effective in plantation areas. The signal capture power is good even though it is placed on a coconut tree where there are several obstacles that block around the module.